Hur påverkar bävern skogens värden? - Sund, Andreas (SLU/School for Forest Management, 2009)
The activities of beavers in forested landscapes affect both ecological and economical values. The creation of the dynamic wetland mosaic associated to beaver activities can even improve the quality of water and have been documented as an important landscape engineer affecting the environment for many species. The local office of Sveaskog in Skinnskatteberg is responsible for the management of large areas of the forests in the County of Västmanland. In this area one of several company’s goals are to create ten new wetlands in their own forests as a part of cooperation with the Swedish bird society and Swedish wetland association. By establishment of an artificial wetland in an old beaver dam, Sveaskog wanted to review the economical and ecological values of the forests in wetlands created by beaver activity. This study considers fifteen sites where beaver activity had been reported. In those sites a 150 m2 large survey circle was examined in each hectare of wetland created of beaver activity. The same area of a circle where measured in the surrounding forest. In those circles the amount of dead wood was measured along with the number of tress with traces of woodpeckers, insect holes, occurrence of lichen and tree living fungus was counted and documented. The number indicated a nature value. All values were compared to the reference survey circles in surrounding forest. The tree species composition within the circle was observed, as well as the position of the dead wood. The results showed a significant difference between the nature values in wet lands created of beaver activity and the surrounding forests. There were significant correlations between nature values associated to trees and dead wood and the age of the wetland created of beaver activity. I found no correlation between nature values and the amount of dead wood or between the tree species composition and the amount of dead wood. The difference of tree species varied from spruce dominated stands in beaver wetlands established in streams impacted by ditches. In beaver wetland established in streams without ditches there was a trend of birch dominated stands. There was a significant difference between the amount of dead wood in wetlands created by beavers and the surrounding conventionally managed forest. The economical gross value of the forest standing in the wetland created by beaver activity differed from 20 000 SEK/ha up to 197 000 SEK/ha, and this study showed that typically ditched productive forest stands were the areas at highest risks for severe tree damages and costs associated to beaver activities.